Förändrad aptering av massaved från 3- till 4-meterslängder vid gallring inom Södra : en systemanalys av effekter från avverkning till levererad virkesråvara - Henriksson, Jakob (SLU/Dept. of Forest Products, 2003)
The costs of logging and of transportation with truck are dominating the total cost of wood delivered at industry. To support the profitability for the members' forestry the processing and handling with the timber has to be as efficient as possible. Increased length of pulpwood in thinning is one conduct that can result in higher productivity and/or lower costs. The study is scaled as a system analysis with the aim to exemplify the differences between working with 3- and 4-meter as standard length of pulpwood, related to biological aspects, timber receipts, cost of logging and cost of transportation with truck. Important aspects are if the change is technically and biologically feasible and economically profitable. The logging analyses in forest show how the timber receipts and cost of logging varying for the different lengths. Out of these effects a different profit before truck road was calculated. The study is based on two monitory stands, one first time thinning and one second time thinning. The thinning grade is about 50 m3fub per ha each. The stands were cross-cut according to price-list of assortment range for the alternatives sawlogs & pulp wood as well as for sawlogs, sawlogs of standard lengths & pulp wood. The transportation with truck, from upper terminal to industry has been studied at varying transport distances as regards capacity and costs in SEK per m3fub. To ensure that the change is technical feasible, a machine operator (harvester and forwarder) and a truck has been operating with 4-meter lengths. The Timber Measurement Association at Mörrum's pulp mill has delivered their point of view of the change. The results show that cross-cut of 4-meter lengths increase the profit before truck road by 135-338 SEK per ha. The 3-meter alternative gives however higher yield and as a result of that higher timber receipts, while 4-meter lengths result in lower logging costs. The lower logging costs with 4-meter lengths are so high that they exceed the increasing timber receipts for the 3-meter lengths. In spite of smaller space (3- instead of 5 loads) the capacity of the transportation with truck is increasing as a result of more efficient loading and unloading. The biological effects are of miner importance. The conclusion out of this study is that using 4-meter as standard length in thinning is economically profitable.